Risk analysis in the investments of construction projects/Rizikos analizės reikšmė statybos investiciniams projektams - Tamošiūnienė, Rima (Journal of Civil Engineering and Management, 1999)
Lithuanian economy transformation into a market economy extremely increased the risk of enterprises. Transition from a producer market to a consumer market caused the technological innovations in construction business. It needs long-term investments. So the management of such investments risk is a problem of today. The paper deals with indentifying conceptual problems of risk and uncertainty definition as well as indicators for the quantitative risk management. Some aspects of the application of the risk management ideology which is thought as risk analysis and risk reduction are discussed. Risk analysis includes methods such as sensitivity analysis, breakeven point analysis, mathematical programming methods, scenario analysis, Monte-Carlo technique etc. There are many types of risk in business. Risks can be classified as external unforeseeable risks, external foreseeable (but not determined) risks, operating risks, technical risks, legal risks etc. The first step in risk management is the risk analysis, then follows the application of risk reduction methods. Article in Lithuanian. First Published Online: 26 Jul 2012